Desenvolvimento e caracterização centesimal, microbiológica e sensorial de hidrolisados protéicos de tilápia do Nilo (Oreochromis niloticus) - Veit, Juliana Cristina (2012)
The Nile tilapia is a specie that has been highlighted in recent years for various reasons, however, during their filleting there is a sub use of its chips, resulting in very rich protein sources waste that could be used in food. An alternative for these waste can be the development of protein hydrolyzed, which are constructed using enzymes that hydrolyze proteins into small peptides and free amino acids, that can be used in diets for patients with difficult or disability in the absorption of intact protein, as hypoallergenic food for liver diseases, as protein supplements and as a flavoring in foods. In this sense, this present study aimed to develop protein hydrolyzed of Nile tilapia V cuts and breaded fish with partial inclusion of hydrolyzed and characterized them with respect to chemical composition, microbiological and sensory. The raw material used to obtain the protein hydrolyzed were Nile tilapia V cuts and commercial enzymes, one obtained from Bacillus (H1) and other extracted from papaya latex (H2). The hydrolyzed were prepared in a simulator reactor consists of a mechanical stirrer and an electrical heater. For the hydrolyze condition control were monitored the pH and temperature until that were optimal enzymatic condition. After some times of hydrolyze, the process ended with the thermal enzyme inactivation and filtration of the obtained products. After that, were determined the hydrolysis degree of each hydrolyzed. To verify their application, three breaded formulation were developed, one without hydrolyzed, one with 8% of hydrolyzed (H1) inclusion and one with 8% of hydrolyzed (H2) inclusion. Were realized moisture, protein, lipids, ash and carbohydrate analysis of the hydrolyzed and breaded. To control the hygienic and sanitary conditions of the final products were carried out microbiological analysis of positive Staphylococcus coagulase, Salmonella sp, thermotolerant coliforms, molds, yeasts, mesophilic and psychrotophic. To verify the breaded acceptation, was carried out the sensorial analysis with 35 volunteer tasters. The determined hydrolysis degrees were 14,76% for H1 and 13,17% for H2. The hydrolyzed showed 81,42 and 70,98% for moisture, 13,61 and 14,62% for protein, 3,45 and 2,78% for lipids and 2,68 and 2,03% for ash, respectively for H1 and H2. The breaded showed 62,32; 64,18 and 65,05% for moisture, 12,36; 12,69 and 13,02% for protein, 2,93; 2,84 and 2,79% for lipids, 1,28, 1,46 and 1,49% for ash and 21,11; 18,83 and 17,65% for carbohydrates, respectively for H1 hydrolyzed, H2 hydrolyzed and without hydrolyzed. With relation to microbiological results, for both as a hydrolyzed as well breaded had values below to the current Brazilian legislation allows. According to sensory analysis all of breaded were good acceptance. So, the enzymatic hydrolysis showed as an efficient process to obtain hydrolyzed protein from a low value added raw material, showing excellent nutritional quality and great hydrolysis degrees which allow its use both as a flavoring in foods such as to treat specific diseases. Moreover, the inclusion of fisheries protein hydrolyzed in fish breaded formulation is a great alternative to partial substitution of meat, as it keeps its nutritional value and are well accepted by consumers and presents good sanitary quality.